Big Data Analytics and Intelligence: A Perspective for Health Care - Tanwar, Poonam; Jain, Vishal; Liu, Chuan-Ming; Goyal, Vishal (Emerald Publishing Limited, 2020)
Big Data Analytics and Intelligenceis essential reading for researchers and experts working in the fields of health care, data science, analytics, the internet of things, and information retrieval.